The Pyruvate Dehydrogenase Complexes: Structure-based Function and Regulation - Patel, Mulchand S.; Nemeria, Natalia S.; Furey, William; Jordan, Frank (The Journal of biological chemistry, 2014)
The pyruvate dehydrogenase complexes (PDCs) from all known living organisms comprise three principal catalytic components for their mission: E1 and E2 generate acetyl-coenzyme A, whereas the FAD/NAD+-dependent E3 performs redox recycling. Here we compare bacterial (Escherichia coli) and human PDCs, as they represent the two major classes of the superfamily of 2-oxo acid dehydrogenase complexes with different assembly of, and interactions among components. The human PDC is subject to inactivation at E1 by serine phosphorylation by four kinases, an inactivation reversed by the action of two phosphatases. Progress in our understanding of these complexes important in metabolism is reviewed.